Comparison of Pain and Mouth Opening in Primary versus Secondary Closure after Surgical Removal of Impacted Mandibular Third Molar - Muhammad Aamir, Tahir Ullah Khan, Muhammad Masood Khan, Muhammad Ishfaq, Mohammad Farooq, Hanif Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare pain score and trismus in primary and secondary closure of surgical wound after removal of impacted mandibular third molar. Study design: Randomized controlled trial. Place and duration of study: Bacha Khan Medical Complex, Gajju Khan Medical College, Shah Mansoor Swabi Pakistan from 1stMay 2020 to 30thJune 2021. Methodology: Fifty patients were divided into two groups i-e group A (Primary closure) and group B (secondary closure). Demographic data (name, age, gender and contact number) was recorded. Pre-operative mouth opening was measured as maximum interincisal distance in millimetres. Pre-operative variables were again re-evaluated on 3rd post-operative day for pain on Visual analogue scale (VAS 0-10) and for mouth opening. Results: Thirty one (62%) patients were males and 19(38%) were females. Overall mean pain score was 2.48±1.90 on visual analogue scale (VAS). Mean age was 30.24±7.64 years while mean post-operative interincisal distance was 43.5±4.717 mm. The difference between Group A and B for both mouth opening ((P=0.03; 95% CI = 0.135, 0.434) and pain (P=0.006; 95% CI = 0.426, 2.453) were statistically significant. Conclusion: When intra operative parameters of impaction difficulty are the same, secondary closure ensures minimal morbidity of pain and trismus as compared to primary wound closure. Keywords: Flap closure; Primary closure; Secondary closure; Impacted third molar